If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3n + 3) = 7(6n + 7) + 1 Reorder the terms: 4(3 + 3n) = 7(6n + 7) + 1 (3 * 4 + 3n * 4) = 7(6n + 7) + 1 (12 + 12n) = 7(6n + 7) + 1 Reorder the terms: 12 + 12n = 7(7 + 6n) + 1 12 + 12n = (7 * 7 + 6n * 7) + 1 12 + 12n = (49 + 42n) + 1 Reorder the terms: 12 + 12n = 49 + 1 + 42n Combine like terms: 49 + 1 = 50 12 + 12n = 50 + 42n Solving 12 + 12n = 50 + 42n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-42n' to each side of the equation. 12 + 12n + -42n = 50 + 42n + -42n Combine like terms: 12n + -42n = -30n 12 + -30n = 50 + 42n + -42n Combine like terms: 42n + -42n = 0 12 + -30n = 50 + 0 12 + -30n = 50 Add '-12' to each side of the equation. 12 + -12 + -30n = 50 + -12 Combine like terms: 12 + -12 = 0 0 + -30n = 50 + -12 -30n = 50 + -12 Combine like terms: 50 + -12 = 38 -30n = 38 Divide each side by '-30'. n = -1.266666667 Simplifying n = -1.266666667
| -162x-82=738 | | x-36=-4x+39 | | 11x+11y=-88 | | 162-82x=738 | | 13/3÷0 | | 11y+11y=-88 | | 3x-6=5+2x | | 10x-4x+4-9= | | Ln(e)= | | N=-2+-3n | | 3-7y=-18-3 | | 2s-(11664/s^2)=0 | | 6(4+a)+4(a-18)=12(2a+3) | | 11z+3=10(22+3) | | x+29ifx=-12 | | 11/2/.25= | | 4,5/0,5n | | 12X+6Y+7Z=6000 | | 4=t/2,5 | | x-9=25+x | | 2(7x-1)-(x-2)= | | -200=20(x+1) | | Cos4x=-sqrt3/3 | | 5y=3478-3c | | 6(k-6)=6(k+2) | | Log(x-5)+log(x-5)=2 | | 27=(x+3)9 | | (x-(-3-i))(x-(-3+i))=0 | | f/6=2,5 | | -4(x-5)=44 | | -87-x+43=-75 | | 5r^4+10r^2+2=0 |